2021
DOI: 10.1111/gcb.15973
|View full text |Cite
|
Sign up to set email alerts
|

Changes in tree drought sensitivity provided early warning signals to the California drought and forest mortality event

Abstract: Climate warming in recent decades has negatively impacted forest health in the western United States. Here, we report on potential early warning signals (EWS) for drought-related mortality derived from measurements of tree-ring growth (ring width index; RWI) and carbon isotope discrimination (∆ 13 C), primarily focused on ponderosa pine (Pinus ponderosa). Sampling was conducted in the southern Sierra Nevada Mountains, near the epicenter of drought severity and mortality associated with the 2012-2015 California… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 67 publications
1
16
1
Order By: Relevance
“…While tree growth is typically well explained by current and previous-year climate, if widespread and frequent droughts persist across the western USA, we may expect weaker correlation between tree-ring widths and previous-year precipitation at the regional scale. While past work has shown loss of correlation between variability in tree growth and temperature indices, that is, "divergence" (Carrer & Urbinati, 2006;D'Arrigo et al, 2008), or increased sensitivity to drought (Keen et al, 2021), our results show divergence in the temporal synchrony between growth and climate may also be widespread, likely due to warmer and drier conditions. Furthermore, we demonstrate altered sensitivity to climate conditions may be more evident in models that do not account for long climate memory (Figure 6), where shifts in importance to more recent temperature conditions (Figure 2b) manifest as increased sensitivity (Figure 6b).…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…While tree growth is typically well explained by current and previous-year climate, if widespread and frequent droughts persist across the western USA, we may expect weaker correlation between tree-ring widths and previous-year precipitation at the regional scale. While past work has shown loss of correlation between variability in tree growth and temperature indices, that is, "divergence" (Carrer & Urbinati, 2006;D'Arrigo et al, 2008), or increased sensitivity to drought (Keen et al, 2021), our results show divergence in the temporal synchrony between growth and climate may also be widespread, likely due to warmer and drier conditions. Furthermore, we demonstrate altered sensitivity to climate conditions may be more evident in models that do not account for long climate memory (Figure 6), where shifts in importance to more recent temperature conditions (Figure 2b) manifest as increased sensitivity (Figure 6b).…”
Section: Discussioncontrasting
confidence: 79%
“…Tree-ring syntheses suggest tree growth responses across most forests reflect greater recent moisture limitation (Babst et al, 2019), and there is limited evidence trees are becoming more sensitive (Keen et al, 2021) and less resilient to drought (e.g. Bose et al, 2020;Serra-Maluquer et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that negative growth trends are common before drought-induced dieback in conifer species (e.g., Camarero et al, 2015aCamarero et al, , 2018Camarero et al, , 2021aCailleret et al, 2017;De Soto et al, 2020;Keen et al, 2022). We observed that growth trends for P. sylvestris and P. nigra were negative in the period 2008−2017 after accounting for age-and SPEI-effects (Figure 4).…”
Section: Discussionmentioning
confidence: 54%
“…Droughts cause abrupt growth reductions in tree growth (Schweingruber, 1986) that can last for several years creating carryover effects or drought legacies (see Anderegg et al, 2015) and impacting drought resilience capacity (Lloret et al, 2011). Importantly, tree growth responses to past droughts may determine the likelihood of dieback and mortality occurrence in the future and be used as early warning signals of tree vulnerability (Camarero et al, 2015a(Camarero et al, , 2021aCailleret et al, 2017;De Soto et al, 2020;Keen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…While biotic influences on radial growth can be minimized through careful tree selection (i.e., dominant trees without signs of pest or pathogen infestation), the use of tree‐ring stable carbon isotopes provides a more direct measure of physiological response to external drivers and a more precise indicator of drought stress than radial growth alone (Friedman et al, 2019; Keen et al, 2021; Leffler & Evans, 1999; Schook et al, 2020). Carbon isotope discrimination (Δ 13 C) in tree‐rings can provide a retrospective measure of leaf gas exchange, integrated at the canopy level, due to its inherent relationship with the ratio of leaf internal CO 2 concentration (C i ) to atmospheric CO 2 concentration, and the preferential uptake of 12 C over 13 C during photosynthesis (Cernusak et al, 2013; Farquhar et al, 1989; Francey & Farquhar, 1982).…”
Section: Introductionmentioning
confidence: 99%